Using Microsoft Office 2011 for the Mac. - Johnson, Yvonne (Using--, 2011)
"Using Microsoft Office for Mac 2011 also has 58 instructional videos that walk you through steps in the book or provide you with additional information that supplements topics in the book. Video instructions cover such topics as using the Scrapbook in Word, creating AutoText entries, creating email signatures, setting recurring appointments and tasks, using conditional formatting in Excel, animating slide elements and applying slide transitions in PowerPoint, and uploading files to a SkyDrive folder. Additionally, 16 audio files also provide you with supplemental information on such topics as creating Automator workflows, macro and security issues, setting up an Exchange email account, editing master slides in PowerPoint, using absolute cell references in Excel, and working with documents on a Sharepoint server."--Resource description page.